Developmental perspectives on the behaviour of missing children: exploring changes from early childhood to adolescence - Woolnough, Penny S. (Psychology, crime & law, 2021)
Despite the inherent vulnerability of missing children and the associated emotional intensity for those affected, there has been no academic exploration of child development and missing behaviour. The current enquiry comprised an examination of police case records to determine how the circumstances and behaviour of missing children varies across early childhood (2-6 years; n = 79; 10.3%), middle childhood (7-11 years; n = 175; 22.9%), and adolescence (12-17 years; n = 512; 66.9%). Children were more likely to go missing in adolescence than early or middle childhood, and more boys than girls were reported missing before adolescence, with the opposite pattern found during adolescence. Adolescents travelled further, took public transport more, and were more likely to be accompanied than those in the younger age groups. Children in the youngest age group were more likely to go missing unintentionally, whereas adolescents were more likely to run away intentionally. Based on these findings it is argued that developmentally informed understanding should contribute to future strategies for preventing and responding to missing children.